Bifunctional Furfuryl Cations Strategy: Three‐Component Synthesis of Enamidyl Triazoles. Issue 1 (30th November 2015) - Yang, Hengtuo; Gou, Jing; Guo, Jiawei; Duan, Dongyu; Zhao, Yu‐Ming; Yu, Binxun; Gao, Ziwei
Abstract: A new multicomponent synthesis of functionalized enamidyl triazoles starting from simple and readily available starting materials is described. A simple treatment of a dichloromethane solution of an azide, amine, and 5‐bromo‐2‐furylcarbinol with a Lewis acid provides the enamidyl triazole in good to high yield. A triple domino sequence, formal [3+2] cycloaddition/ring‐opening/amidation, is involved in this new skeleton‐generating reaction. Abstract : Heterocycle reassembling : 5‐Halofurylcarbinol can serve as a bifunctional platform to react with an azide and amine by a Lewis acid promoted three‐component reaction. It involves a novel formal [3+2] cycloaddition/ring‐opening/amidation cascade, enabling the expedient and efficient construction of a diverse set of highly functional enamidyl triazoles (see scheme).